Rapid Purification and Partial Characterization of an Extracellular Enantioselective Lipase from Aspergillus niger - Malle, Dominggus; Garingan, Gina; Peralta, Milagros; Revilleza, Maria Jamela (ANNALES BOGORIENSES, 2008)
Lipases  [EC.  3.1.1 .3]  are  capable  of hydrolyzing  ester  bonds  of triglycerides  and  have  received  much attention  from  protein  researchers  after  these  enzymes  have  shown  potential  applications  such  us,  in  the manufacture of commercially important chiral drugs due to their enantioselectivity properties. A novel  extracellular lipase  produced  by Aspergillus  niger was  purified  and  partially  characterized.  Using  the  culture medium  as crude extract, the Lipase was purified  to 25 .7  folds after Ultrafiltration and DEAE ion exchange chromatography. The enzyme was characterized to have optimum activity at neutral pH and at 30-35°C, while its kinetic parameters, Vmax and Km, were determined  to  be  L80 U/mL/min  and 0.2 mL , respectively. SDS-PAGE analysis  revealed  the presence of at  least two  bands  (±87  and ±72  kDa), while  native  PAGE  showed  a  single  band.  The  two  bands could represent subunits  in  a complex or isoforms of the enzyme. The use of  the enzyme  in  th  hydrolysis of a racemic  mixture  of 2-arylpropionic  butyl  ester  analyzed  after HPLC demonstrated  an  apparent predominant enantioselectivity for the S (+) enantiomer. Thus, this lipase is a promising enzyme for the chiral drug preparation of  single enantiomer of 2-arylpropionic acid (ibuprofen) .Keywords: Iipase, Aspergillus niger, purification, enantioselectivity, chiral  drug, ibuprofen